2013
DOI: 10.1093/ejcts/ezt541
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preoperative symptoms on outcomes after valve repair for degenerative aortic insufficiency

Abstract: In asymptomatic patients with severe degenerative AI, AVr is associated with excellent long-term outcomes, while symptoms are associated with reduced long-term survival. In dilated LV, freedom from reoperation is lower. If feasible, early AVr is recommended in experienced centres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…However, after six months of AV replacement, the mean gradient had reduced. A previous study reported a similar reduction in mean AV gradient to 12.0 ± 11.9 and 16.8 ± 11.1 mmHg after 45 months of AV repair in patients who had preoperative peak aortic gradient of <20 and ≥20 mmHg, respectively [27].…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…However, after six months of AV replacement, the mean gradient had reduced. A previous study reported a similar reduction in mean AV gradient to 12.0 ± 11.9 and 16.8 ± 11.1 mmHg after 45 months of AV repair in patients who had preoperative peak aortic gradient of <20 and ≥20 mmHg, respectively [27].…”
Section: Discussionsupporting
confidence: 55%
“…However, after six months of AV replacement, the mean gradient had reduced. A previous study reported a similar reduction in mean AV gradient to 12.0 ± 11.9 and 16.8 ± 11.1 mmHg after 45 months of AV repair in patients who had preoperative peak aortic gradient of <20 and ≥20 mmHg, respectively [ 27 ]. In patients with rheumatic mitral stenosis, the mean transvalvular gradient was reported to be 7 mmHg in mild-to-moderate mitral stenosis and 14 mmHg in severe mitral stenosis, which was reduced to 4 and 6 mmHg, respectively, post-valvuloplasty [ 28 ].…”
Section: Discussionmentioning
confidence: 64%
“…The risks of aortic valve reoperation were 10% at 5 years and 21% at 10 years. Vohra and colleagues 3 reported similar outcomes in their series of 274 aortic valve repairs in the course of 14 years for severe aortic insufficiency. Their operative mortality was 0%, and there was a trend toward improved 10-year survival among the patients who underwent surgery without symptoms versus those who had symptoms (100% vs 77%; P ¼ .1).…”
mentioning
confidence: 69%
“…Should this matched cohort serve as a benchmark for judging AV repair procedures? The average age in the total Brussels AV repair cohort is approximately 50 years, 4 which poses the question of whether the expected AV repair benefits should be the same across all age groups.…”
Section: Repair or Replace The Aortic Valve? More Questions No Answementioning
confidence: 99%